2011
DOI: 10.1515/cclm.2011.634
|View full text |Cite
|
Sign up to set email alerts
|

New serum biomarkers for detection of tuberculosis using surface-enhanced laser desorption/ionization time-of-flight mass spectrometry

Abstract: The data suggested a potential application of SELDI-TOF MS as an effective technology to profile serum proteome, and with pattern analysis, a diagnostic model comprising three potential biomarkers was indicated to differentiate people with TB and healthy controls rapidly and precisely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…However, the low detection rate of sputum smear‐positive and time‐consuming of sputum culture have restricted the diagnosis of pulmonary TB and discouraged early treatment of the disease. Research in our laboratory on TB biomarkers has demonstrated different peaks between TB and other lung diseases (2024, 8007, and 8598 Da) previously , but further studies are needed to identify these mass peaks. We also found that APOCII, CD5L, HABP2, and RBP4 may be potential pulmonary TB biomarkers, however, the experiment did not set the group for differential diagnosis.…”
Section: Discussionmentioning
confidence: 95%
“…However, the low detection rate of sputum smear‐positive and time‐consuming of sputum culture have restricted the diagnosis of pulmonary TB and discouraged early treatment of the disease. Research in our laboratory on TB biomarkers has demonstrated different peaks between TB and other lung diseases (2024, 8007, and 8598 Da) previously , but further studies are needed to identify these mass peaks. We also found that APOCII, CD5L, HABP2, and RBP4 may be potential pulmonary TB biomarkers, however, the experiment did not set the group for differential diagnosis.…”
Section: Discussionmentioning
confidence: 95%
“…But the authors did not establish the differential diagnosis groups, and verified two serum markers in a large sample. In our laboratory, Liu et al [18] detected specific protein markers for the diagnosis of TB, and established a model based on the three biomarkers (2024, 8007, 8598 Da) to differentiate between patients with TB and other lung diseases by using surface enhanced laser desorption/ionization - time of flight - mass spectrometry (SELDI-TOF-MS). However, due to poor reproducibility of results, further study is needed for screening pulmonary TB biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed diagnosis results in more extensive disease, complications, and increased mortality. 16 Spinal TB usually presents in a slowly indolent manner with nonspecific clinical presentations, making the diagnosis a great challenge for clinicians. A definite diagnosis of spinal TB depends on the demonstration of M. tuberculosis by culture from biopsy specimens.…”
Section: Discussionmentioning
confidence: 99%